2019
DOI: 10.1093/jn/nxy224
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with DHA Modifies the Response of MDA-MB-231 Breast Cancer Cells and Tumors from nu/nu Mice to Doxorubicin through Apoptosis and Cell Cycle Arrest

Abstract: Background Docosahexaenoic acid (DHA) has been shown to reduce growth of breast cancer cells in vitro and in vivo; it may also benefit the action of cytotoxic cancer drugs. The mechanisms for these observations are not completely understood. Objectives We sought to explore how pretreatment of MDA-MB-231 breast cancer cells with DHA alters gene expression with doxorubicin (DOX) treatment and confirm that feeding DHA to tumor-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 61 publications
1
54
0
Order By: Relevance
“…Paraffin-embedded tumor sections were deparaffinized as previously described (Newell et al, 2019a) and stained with Harris Modified Hematoxylin and Eosin Y (H&E, Fisher Scientific, Edmonton, AB, Canada) to assess morphology and regions of necrosis. Slides were scanned with an Aperio Scanner and relative percent of necrosis was determined with Image Scope software.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Paraffin-embedded tumor sections were deparaffinized as previously described (Newell et al, 2019a) and stained with Harris Modified Hematoxylin and Eosin Y (H&E, Fisher Scientific, Edmonton, AB, Canada) to assess morphology and regions of necrosis. Slides were scanned with an Aperio Scanner and relative percent of necrosis was determined with Image Scope software.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…MDA-MB-231 cells, representative of TNBC, have more aggressive growth and an intermediate response to chemotherapy (Holliday and Speirs, 2011). The antitumorigenic properties of n-3 long-chain polyunsaturated fatty acids (LCPUFA), specifically docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), have been shown in both cell culture and animal studies (Chajes et al, 1995;D'Eliseo and Velotti, 2016;Ewaschuk et al, 2012;Newell et al, 2019a;Newell et al, 2019b;Rose et al, 1995;Schley et al, 2007). DHA has displayed greater cytotoxicity than EPA at the same concentration in MDA-MB-231 and MCF-7 cells (Barascu et al, 2006;Ewaschuk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, ESCs derived from fad3b (has similar functions as Fat-1 [40]) transgenic mice showed a much slower cell cycle with an increased n-3 PUFA content in the cells [41]. In other studies, n-3 PUFAs could also inhibit the proliferation of different kinds of cancer cells by regulating their cell cycle [42][43][44][45]. Therefore, Fat-1 expression cells may also have a lower proliferation rate than Fat-1 silencing cells or cells in wild type sheep.…”
Section: Discussionmentioning
confidence: 91%
“…Doxorubicin is another first-line chemotherapy used in TNBC ( 103 ). Studies showed DHA enhanced the efficacy of doxorubicin in TNBC cells and an in vivo mouse model ( 55 ). Single agent treatment with either doxorubicin or DHA (60 μM) decreased MDA-MB-231 cell viability.…”
Section: Fish Oil and Tnbc: Reviewmentioning
confidence: 99%